THE EFFECT OF SCIENTIFIC INQUIRY LEARNING MODEL TO SCIENCE PROCESS SKILL ON DYNAMIC FLUID TOPIC OF GRADE XI SEMESTER II SMA DHARMA PANCASILA MEDAN A.Y 2016/2017 - Nida'ul Khairiyah; Mara Bangun Harahap (INPAFI (Inovasi Pembelajaran Fisika), 2017)
This research aims to analyze the effect of scientific inquiry learning model to science process skills on dynamic fluid topic grade XI semester II SMA Dharma Pancasila Medan academic year 2016/2017. The type of this research was quasi experiment, with experiment class used scientific inquiry learning and control class used conventional learning. The population was all of the classes XI. Sample was taken with random sampling technique. The instrument used to determine student’s science process skills in dynamic fluid matter in form of experiment test with two observer and observation activity of student and the instrument had been validated and fulfilled to validator expert and reliability of test. Based on the data tabulation obtained the result of science proces skill of student pre-learning in experiment class 32.06 and 31.35 in control class and the result of science process skills post-learning in experiment class 78.13 and 50.91 in control class. Based on t testing, it can be conclude that science process skills of student using scientific inquiry learning model was better than conventional learning.Keywords: Scientific inquiry learning model, science process skills